INVENTARISASI GULMA PADA PERKEBUNAN COKELAT DESA PAJAR BULAN KABUPATEN LAHAT PROVINSI SUMATERA SELATAN - Dewi, Rosanti (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2013)
Research of inventarisation of weeds in caccao crop was conducted on Februari till Maret 2012 at Pajar Bulan village in Lahat Recency, Sumatera Selatan Province, to saw diversity weed species. This research utilited the direct observation with Plot Analisys Methods in 1 hectares area during one week. The result showed 8 species are Euphorbia hirta (Patikan kebo), Centella asiatica (kaki kuda), Ageratum conyzoides (bandotan), Synedrella nodiflora (jotang kuda), Crassocephalum crepidioides (sintrong), Fimbristylis annua (teki), Cyperus rotundus (teki ladang) dan Caladium sp (keladi), from 1 division, 2 class, 5 order, 5 family, 8 genera. Key words : cacao crop, weeds, inventarisation